Penerapan Terapi Kombinasi terhadap Sensitivitas Kaki Lansia Diabetes Mellitus di Pucangsawit Surakarta: Terapi Kombinasi Senam Kaki dan Rendam Air Hangat - Nirwana Aryani; Tri Susilowati (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2024)
Background: DM cases in Central Java are in fifth highest positian in Indonesia with a prevalence of 2.0%. Pucangsawit Community Health Center is a sub-district with 979 DM sufferers in 2022. The most cases are in Pucangsawit Village with 421 cases of DM. DM sufferers, especially the elderly, experience complications from mild to severe neuropathy complications resulting in loss of sensation in the lower extremities due to impaired blood circulation in the leg area. Loss of sensation the periphery of the feet is an early early symptom of diabetic ulcer. Objective: To describe the results of implementation before and after the application of kombması therapy, foot exercises and warm water soaks on foot sensitivity in elderly people with DM. Method: This type of research is a descriptive case study. Results: Before the combination therapy, the foot sensitivity of both respondents was low, after the combination therapy, the foot sensitivity of both respondents experienced an increase with the score of each respondent being 4. Conclusion: There is a comparison of the number of increases in the number of foot sensitivity scores of both respondents the increase in the number of respondent 1 is bigger than for respondent 2 with a difference of 1 point in both legs